Metonymic Similes in Newspaper Film Reviews - Vardanyan, Irina (Armenian Folia Anglistika, 2011)
The article analyses the role of the metonymic simile in newspaper film reviews. To make the speech more impressive reviewers turn to the use of similes. The type of simile prevailing in film reviews is metonymic simile which is based on associations, usually limited to the combination of physical and some other features (size, form, scale, color). Any simile in a film review carries out the functions of impact, cognition, persuasion and propaganda.